Oxygen reduction reaction on carbon supported dispersed platinum nanoparticles and extended platinum surfaces - Taylor, Susan M (Department of Chemical Engineering, 2016)
To date, the cost of high platinum loadings in polymer electrolyte fuel cells (PEFCs) remains one of the main deterrents preventing their broad commercialisation. The reaction of interest in this work is the oxygen reduction reaction (ORR) occurring at the cathode side of the PEFC. The ORR has been studied at great length owing to the sluggish kinetics of this reaction and thus the necessity of the higher platinum loadings required on the cathode side of the PEFC. Platinum particle size and surface morphology are thought to be directly related to the catalytic activity of platinum towards the ORR (Mayrhofer et al., 2005) A better understanding of the effects of platinum particle size and surface morphology on the mechanism and kinetics of the ORR is critical if platinum loadings are to be reduced whilst maintaining the US Department of Energy (DoE) target performance levels (Schwanitz et al., 2012). This study focuses on the effects of platinum surface morphology on ORR activity by the development of platinum supported carbon electrodes. The surface morphology was modified by varying the platinum loading, such that the surface was taken from isolated nanoparticles to an extended surface. The effects of the changes in surface morphology and particle size on the ORR were then investigated. First a model electrode system was developed by magnetron sputter deposition of platinum onto a carbon black (VulcanXC72) surface supported on a glassy carbon electrode. The model system was then translated into a practical system, whereby platinum supported on carbon catalysts were prepared by metal-organic chemical vapour deposition (MOCVD) with increasing weight percentages of platinum. Similar trends were observed for the MOCVD catalyst system and the model electrode system. The trends of particular interest were the effects of platinum loading on hydrogen peroxide formation during the ORR and the double voltammeric CO oxidation peak observed with increased platinum loading during CO stripping voltammetry experiments. Hydrogen peroxide formation was observed at potentials below 0.8 V vs. SHE/RHE and it was found that hydrogen peroxide formation was predominant on dispersed platinum nanoparticles compared with platinum agglomerates. This is most likely related to peroxide species, a partial reduction product from oxygen to water, being able to desorb from the active surface without being further reduced to water on an adjacent site as the inter-particle distance is greater for the low loading samples relative to the higher loading samples in both systems. A clear indication of differing surface morphology between the low and high loading samples was observed by the double voltammeric peak detected during CO stripping voltammetry experiments. The low potential peak attributed to platinum agglomerates was seen to increase in amplitude as platinum loading increased. The corresponding high potential peak attributed to isolated nanoparticles, decreased in amplitude with increasing platinum loading. This observation alludes to an increase in particle agglomeration with platinum loading, and physical characterisation methods such as TEM and XRD showed an increase in the average particle size with increasing platinum loading, which supports the CO stripping voltammetry findings. The findings indicate a profound dependence of the ORR on platinum particle size and surface morphology. A better insight into these properties could assist in improved catalyst design and the enhancement of platinum utilisation and ORR activity of platinum.